2005
DOI: 10.1111/j.1745-4514.2005.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin a in Turkish Wines

Abstract: In this research, 47 wine samples produced from 2001 to 2002 harvest period in four Turkish regions were analyzed for the presence of ochratoxin A (OTA). Based on the results, the OTA levels of red wines are generally higher than those of white and rose wines. However, the wines from two wine regions (Aegean and Thrace) are much more contaminated with OTA compared with the others. 5 Corresponding

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…A gradient in OTA concentration is usually recognized, correlated with color, and, therefore, to the wine production process, with OTA levels diminishing from red through rose´to white wine. Another common finding in the majority of surveys is the higher incidence level and concentration of OTA in wines originated from southern vis-a-vis northern regions of production (Visconti et al 1999;Otteneder and Majerus 2000;Pietri et al 2001;Soleas et al 2001;European Commission 2002;Bellı´et al 2004;Blesa et al 2004;Ng et al 2004;Rosa et al 2004;Anli et al 2005;Burdaspal and Legarda 2007;Mateo et al 2007;Valero et al 2008;Visconti et al 2008). Nevertheless, other studies did not reach the same conclusions (Shephard et al 2003;Stefanaki et al 2003).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…A gradient in OTA concentration is usually recognized, correlated with color, and, therefore, to the wine production process, with OTA levels diminishing from red through rose´to white wine. Another common finding in the majority of surveys is the higher incidence level and concentration of OTA in wines originated from southern vis-a-vis northern regions of production (Visconti et al 1999;Otteneder and Majerus 2000;Pietri et al 2001;Soleas et al 2001;European Commission 2002;Bellı´et al 2004;Blesa et al 2004;Ng et al 2004;Rosa et al 2004;Anli et al 2005;Burdaspal and Legarda 2007;Mateo et al 2007;Valero et al 2008;Visconti et al 2008). Nevertheless, other studies did not reach the same conclusions (Shephard et al 2003;Stefanaki et al 2003).…”
Section: Introductionmentioning
confidence: 78%
“…This gradient was also observed in similar studies from Italy (Pietri et al 2001;Perrone et al 2007), Spain (Burdaspal and Legarda 2007;Valero et al 2008), and limited surveys in Greece (Soufleros et al 2003;Stefanaki et al 2003;Melletis et al 2007), and Turkey. However, Turkish study has shown that wines from the Thrace and Aegean coastal regions in the west were more contaminated than those originating from the eastern mainland of Anatolia (Anli et al 2005). Climatic conditions after ve´raison of the grapes and during ripening may be responsible for this difference, where the wet and hotter profile at the Mediterranean coast favors a higher incidence of growth and OTA production by A. carbonarius (Battilani et al 2006;Blesa et al 2006;Visconti et al 2008).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The cartridge was washed with 10 mL of toluene: methanol (97:3, v/v). After eluting with 10 mL of toluene: acetic acid (90:10, v/v), it was evaporated to dryness and dissolved in 1 mL of the mobile phase 2,3 .…”
Section: Sample Preparationmentioning
confidence: 99%
“…In Greece, more than 66% of wine samples showed detectable OTA levels and both red and sweet wines showed the highest levels [178][179][180]. More than 50% of the samples analyzed in Cyprus and Turkey, respectively, had detectable levels of the toxin [181,182].…”
Section: Occurrence Of Ota In Winementioning
confidence: 99%